2019
DOI: 10.3847/1538-4357/ab1cba
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling Molecular Clouds toward Bipolar H ii Region G8.14+0.23

Abstract: Most recent numerical simulations suggest that bipolar H ii regions, powered by O-type stars, can be formed at the interface of two colliding clouds. To observationally understand the birth of O-type stars, we present a detailed multi-wavelength analysis of an area of 1 • × 1 • hosting G8.14+0.23 H ii region associated with an infrared bipolar nebula (BPN). Based on the radio continuum map, the H ii region is excited by at least an O-type star, which is located toward the waist of the BPN. The NANTEN2 13 CO li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 123 publications
0
12
0
Order By: Relevance
“…Several bipolar H II regions are associated with the star formation taking place in the flat or sheet-like cold molecular material delineating the waist of the nebula (Dewangan et al 2016(Dewangan et al , 2019. Fukuda & Hanawa (2000) suggested that the expansion of an H II region near a filamentary molecular cloud can generate sequential waves of star formation.…”
Section: H 2 Emissions Not Associated With Mho 1502: Thementioning
confidence: 99%
“…Several bipolar H II regions are associated with the star formation taking place in the flat or sheet-like cold molecular material delineating the waist of the nebula (Dewangan et al 2016(Dewangan et al , 2019. Fukuda & Hanawa (2000) suggested that the expansion of an H II region near a filamentary molecular cloud can generate sequential waves of star formation.…”
Section: H 2 Emissions Not Associated With Mho 1502: Thementioning
confidence: 99%
“…The first cluster to be identified as a possible collision object was Westerland 2, which harbors two associated clouds with a velocity difference of 20 km s −1 (Furukawa et al 2009;Ohama et al 2010) approximately. Other recent observations by Fukui et al (2014), Torii et al (2015), Baug et al (2016), Dewangan & Ojha (2017), Dewangan et al (2018Dewangan et al ( , 2019, Issac et al (2020) have also detected CCCs in the high-mass star forming regions.…”
Section: Introductionmentioning
confidence: 73%
“…In the CCC process, young stellar clusters and massive stars can be formed at the intersection of two molecular clouds or the shock-compressed interface layer (e.g., Habe & Ohta 1992;Anathpindika 2010;Inoue & Fukui 2013;Takahira et al 2014;Haworth et al 2015a,b;Torii et al 2017;Bisbas et al 2017, and references therein). In the CCC site, one may observationally find the spatial and velocity connections of two molecular clouds (e.g., Torii et al 2017;Dewangan 2017;Dewangan & Ojha 2017;Dewangan et al 2017bDewangan et al , 2018aDewangan et al , 2019. In the position-velocity map, one may also trace bridging features between two molecular clouds, which enable us to infer the association of the two clouds (e.g., Haworth et al 2015a,b).…”
Section: Star Formation Scenariosmentioning
confidence: 99%
“…It may also hint the presence of a compressed layer of gas due to two colliding clouds/flows (e.g., Haworth et al 2015a,b;Torii et al 2017). Furthermore, one may also observe a complementary spatial distribution of two clouds in the CCC site (e.g., Torii et al 2017;Fukui et al 2018;Dewangan et al 2018cDewangan et al , 2019, which is related to the spatial fit of "Key/intensity-enhancement" and "Cavity/Keyhole/intensity-depression" features.…”
Section: Star Formation Scenariosmentioning
confidence: 99%